2013
DOI: 10.1117/12.2028651
|View full text |Cite
|
Sign up to set email alerts
|

Learning transmodal person detectors from single spectral training sets

Abstract: Annotating data for training a person detector is a tedious procedure. Therefore it is worthwhile to use freely available datasets. When detecting in the infrared spectrum it is not obvious that person images from the visible spectrum can be used to train a detector operable in IR. We show that it is possible to train a transmodel detector, which can be used to detect in IR as well as in the visible spectrum. Therefor we use integral channel features in combination with boosting based feature selection, in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A non-maximum suppression is then used to group positive classifications to the final detections. A similar pipeline is applied in later pedestrian detection methods based on integral channel features (Dollár et al, 2009(Dollár et al, , 2014Benenson et al, 2012), which have been shown to work also in infrared images (Kieritz et al, 2013).…”
Section: Image-based Pedestrian Detectionmentioning
confidence: 99%
“…A non-maximum suppression is then used to group positive classifications to the final detections. A similar pipeline is applied in later pedestrian detection methods based on integral channel features (Dollár et al, 2009(Dollár et al, , 2014Benenson et al, 2012), which have been shown to work also in infrared images (Kieritz et al, 2013).…”
Section: Image-based Pedestrian Detectionmentioning
confidence: 99%
“…3: For person detection several feature channels are computed. The detection is based on decision trees using integrals over the different feature channels [15], [16]. A soft-cascade is used to speed up the detection.…”
Section: A Person Detectionmentioning
confidence: 99%
“…An outline of the person detector can be seen in Figure 3. Detection is done by a sliding window approach using a classifier consisting of weighted decisions trees which are selected by boosting [14], [15]. Each node of a tree uses the sum of a fixed region I of a feature channel to make its decision [16].…”
Section: A Person Detectionmentioning
confidence: 99%
“…Furthermore, structures on the persons clothing or other surfaces are not captured in IR which makes IR advantageous for appearance based methods. For the spatial domain Kieritz et al showed that a person detector based on Integral Channel Features (ICFs) provides promising results in both, the visible and the infrared spectrum [3]. Action recognition systems however operate in the spatiotemporal domain.…”
Section: Introductionmentioning
confidence: 99%